Three-dimensional localization versus fluoroscopically only guided ablations: A meta-analysis*. (August 2013) - Shurrab, Mohammed; Laish-Farkash, Avishag; Lashevsky, Ilan; Morriello, Florence; Singh, Sheldon Michael; Schilling, Richard John; Wijeysundera, Harindra Channa; Pinter, Arnold; Newman, David; Crystal, Eugene
Abstract: Objectives. Data regarding efficacy and safety of three-dimensional localization systems (3D) are limited. We performed a meta-analysis of randomized trials comparing combined fluoroscopy- and 3D guided to fluoroscopically-only guided procedures. Design. A systematic search was performed using multiple databases between 1990 and 2010. Outcomes were acute and long-term success, ablation, procedure and fluoroscopic times, radiation dose (RD), and complications. Results. Thirteen studies involving 1292 patients were identified. 3D were tested against fluoroscopic guidance in 666 patients for supraventricular tachycardia (SVT), atrial flutter (AFL), atrial fibrillation (AF), and ventricular tachycardia (VT). Acute and long-term freedom from arrhythmia was not significantly different between 3D and control for AFL (acute success, 97% vs. 93%, p = 0.57; chronic success, 93% vs. 96%, p = 0.90) or for SVT (acute success, 94% vs. 100%, p = 0.36; chronic success, 88% vs. 88%, p = 0.80). A shorter fluoroscopic time was achieved with 3D in AFL (p < 0.001) and in SVT (p = 0.002). RD was significantly less for both AFL (p = 0.002) and SVT (p = 0.01). Ablation and procedure time and complications were not statistically different. Conclusions. Success, procedure time, and complications were similar between fluoroscopy- and 3D-guided ablations. Fluoroscopic time and RD were significantly reduced for ablation of AFL and SVT with 3D.